Patients with Borderline Personality Disorder in Emergency Departments - Shaikh, Untara; Qamar, Iqra; Jafry, Farhana; Hassan, Mudasar; Shagufta, Shanila; Odhejo, Yassar Islamail; Ahmed, Saeed (Frontiers in Psychiatry, 2017)
Borderline Personality Disorder (BPD) patients, when in crisis, are frequent visitors of emergency departments (EDs). When these patients exhibit symptoms such as aggressiveness, impulsivity, intense anxiety, severe depression, self-harm, and suicidal attempts or gestures, diagnosis, and treatment of the BPD becomes challenging for ED doctors. This review will, therefore, outline advice to physicians and healthcare providers who face this challenging patient population in the EDs. Crisis intervention should be the first objective of clinicians when dealing with BPD in the emergency. For the patients with agitation symptom specific pharmacotherapy is usually recommended, while for non-agitated patients, short but intensive psychotherapy especially dialectal behavior therapy (DBT) has a positive effect. Although various psychotherapies, either alone or integrated, are preferred modes of treatment for this group of patients, the effects of psychotherapies on BPD outcomes are small to medium. Proper risk management along with developing a positive attitude and empathy towards these patients will help them in normalizing in an emergency setting after which treatment course can be decided.